Estudo histomorfológico dos mecanorreceptores e terminações nervosas livres do ligamento colateral ulnar da metacarpo falangeana do polegar humano - Farias Júnior, Diogo Araújo De (2020)
Thumb ulnar collateral ligaments (LCUP) are among the most common lesions on the hand, accounting for about 86% of all thumb ligament lesions. When untreated, they can be cause for pain, functional limitation and osteoarthritis in the metacarpophalangeal of the thumb. Five ulnar collateral ligaments from the thumb were removed from frozen, unidentified corpses, with an apparent age between 50 and 70 years. Ligaments with degenerative signs were removed from the sample. The main portion of the ulnar collateral ligament of the thumb was studied using HE stains, Masson, immunofluorescence with PGP 9.5 and Alexa Fluor 488. The stains in HE and Masson were efficient for the study of the structural composition of the LCUP. Immunofluorescence with PGP 9.5 and Alexa Fluor 488 allied to laser confocal microscopy was fundamental in visualizing nerve tissue. Free nerve endings, multifilamentated nerve endings, Ruffin-Like and non-classifiable oval and rounded structures), as well as vascular tissue in the proximal, middle and distal portions of the LCUP were identified. Connective tissue with well organized parallel fibers were well delimited between the nerve endings. We conclude that the presence of nerve endings in the ulnar collateral ligament of the thumb strongly suggests its participation in the stabilization and proprioception of this joint. Future studies including degenerate LCUP may contribute to a better understanding of alterations in histological and anatomic-functional structure, secondary to degenerative processes, correlating with the data obtained in this study.